2006
DOI: 10.1210/en.2005-1139
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Induces an Intracellular Calcium Increase by a Nongenomic Mechanism in Cultured Rat Cardiac Myocytes

Abstract: Androgens are associated with important effects on the heart, such as hypertrophy or apoptosis. These responses involve the intracellular androgen receptor. However, the mechanisms of how androgens activate several membrane signaling pathways are not fully elucidated. We have investigated the effect of testosterone on intracellular calcium in cultured rat cardiac myocytes. Using fluo3-AM and epifluorescence microscopy, we found that exposure to testosterone rapidly (1-7 min) led to an increase of intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 55 publications
3
101
0
1
Order By: Relevance
“…104 , 105 The upregulation of androgen receptor that we observed within the PNA heart may alter the electrophysiology of the cardiomyocytes of the left ventricle by altering expression of receptors involved in the regulation of membrane potential. 106 , 107 Androgens may promote the development of cardiomyopathy by upregulating potassium channel regulatory subunits and reducing cardiomyocyte repolarization. 108 , 109 Indeed, the enlarged walls and decreased cross-sectional area of the left ventricle in the PNA animals resembles early-stage concentric cardiac hypertrophy, although mRNA expression of markers of cardiac hypertrophy were unchanged in PNA animals.…”
Section: Discussionmentioning
confidence: 99%
“…104 , 105 The upregulation of androgen receptor that we observed within the PNA heart may alter the electrophysiology of the cardiomyocytes of the left ventricle by altering expression of receptors involved in the regulation of membrane potential. 106 , 107 Androgens may promote the development of cardiomyopathy by upregulating potassium channel regulatory subunits and reducing cardiomyocyte repolarization. 108 , 109 Indeed, the enlarged walls and decreased cross-sectional area of the left ventricle in the PNA animals resembles early-stage concentric cardiac hypertrophy, although mRNA expression of markers of cardiac hypertrophy were unchanged in PNA animals.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2011) found that testosterone suppresses oxidative stress via androgen receptor-independent pathway in murine cardiomyocytes. In cultured cardiac myocytes, testosterone induced a rapid and nongenomic intracellular Ca 2C release through activation of a plasma membrane androgen receptor associated with the PTX-sensitive G protein-phospholipase C/IP3 signaling pathway (Vicencio et al 2006). Bourghardt et al (2010) found that testosterone atheroprotection was androgen receptor-dependent as well as androgen receptor-independent in male mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this pathway facilitates the hydrolysis of phosphatidylinositol 4,5-bisphosphate by phospholipase C, thereby generating diacylglycerol and IP 3 . IP 3 mediates opening of IP 3 receptors in the sarcoplasmatic reticulum, which in turn produce rapid (1-5 min) Ca 2+ release (Vicencio et al, 2006). Similar effects of testosterone have been identified in T-cells, skeletal muscle and neuroblastoma cells (Benten et al, 1999;Estrada et al, 2003Estrada et al, , 2006.…”
Section: Integrated Model For Androgen Actionmentioning
confidence: 62%
“…However, these responses involve the generation of different patterns of Ca 2+ signals and also in the activation of complementary Ca 2+ -dependent pathways. Thus, in addition to the classical mechanism of steroid action in cardiac cells, androgens activate additional specific signal transduction pathways (Altamirano et al, 2009;Vicencio et al, 2006). An interesting hypothesis is that these second messenger cascades may ultimately serve to modulate the transcriptional activity of the intracellular androgen receptor and its associated global response.…”
Section: Mechanism Of Androgen Actionmentioning
confidence: 99%
See 1 more Smart Citation